Célébration du 24 avril au siège de la FEANF á Paris par le Comité de Liaison des Etudiants anticolonialiste. CE de L'UGEMA
Célébration du 24 avril au siège de la FEANF á Paris par le Comité de Liaison des Etudiants anticolonialiste. CE de L'UGEMA.